2020
DOI: 10.1021/acs.jpcb.0c01199
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding in the Liquid State of Linear Alcohols: Molecular Dynamics and Thermodynamics

Abstract: Linear monohydroxy alcohols are strongly hydrogen-bonded liquids that are considered to be homologues of water. Here, we report ab initio molecular dynamics simulations of the liquid alcohols, methanol to pentanol, and from the combined radial− angular probability distribution of the intermolecular O•••O distances and HO•••O angles determine the geometrical parameters that define the hydrogen bonds in these systems.The key feature of hydrogen bonds in the liquid alcohols, irrespective of the size of the alkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…42 It had been shown earlier from a study of the liquid linear alcohols that the dispersion-corrected BLYP functional is superior to the other functionals, for example, PBE or HCTH in the description of hydrogen-bonded liquids. 36 The It has also been reported that it provides a cost-effective ab initio method for capturing the water solvation structure and dynamics. 43 A time step of 4 au (0.096 fs) and a fictitious electron mass value of 400 au were used to integrate the equations of motion.…”
Section: ■ Simulation Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…42 It had been shown earlier from a study of the liquid linear alcohols that the dispersion-corrected BLYP functional is superior to the other functionals, for example, PBE or HCTH in the description of hydrogen-bonded liquids. 36 The It has also been reported that it provides a cost-effective ab initio method for capturing the water solvation structure and dynamics. 43 A time step of 4 au (0.096 fs) and a fictitious electron mass value of 400 au were used to integrate the equations of motion.…”
Section: ■ Simulation Methodologymentioning
confidence: 99%
“…Hydrogen bond formation is subsequently considered as the passage from a state where donor−acceptor EG pairs are randomly oriented to the one where they are strongly oriented, and the thermodynamics of bond formation is estimated from the PMF for this process (eq 2). 34,36,54…”
Section: ■ Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, they have been found as food additives, industrial precursors in many reactions, as well as drugs and drug matrices, e.g., [5][6][7][8]. Linear monohydroxy alcohols are organic molecules containing a hydrogen atom attached directly to an oxygen in the -OH group [9]. Therefore, they are capable of forming hydrogen bonds, both as proton donors and acceptors and become strongly hydrogen-bonded liquids [10].…”
Section: Introductionmentioning
confidence: 99%